The analysis of institutional environment in the area of product market competition in the new EU member states: What do the data say about the models of capitalism emerging in the CEE countries? - Mariusz Próchniak (International Journal of Management and Economics, 2018)
The paper analyzes the institutional architecture and the effects of product market competition in 11 countries of Central and Eastern Europe (CEE). The aim of the research was to find out how similar or dissimilar are the CEE countries in the area of product market competition compared with the four models of capitalism prevailing in Western Europe: the Anglo-Saxon (liberal) model (the UK), the continental model (Germany), the Scandinavian (Nordic) model (Sweden), and the Mediterranean one (Spain). The research method involves calculations of the coefficients of similarity and the analysis of polygons, being the extension of our own concept of the hexagons of similarity. The dynamic approach adopted in this study allows to examine the path dependence in order to assess how the institutional environment evolved over time. The analysis indicates that almost all CEE countries were the most similar to the Mediterranean model of capitalism represented by Spain. However, the variety of results for the individual variables is also a proof that the model of capitalism prevailing in CEE in the area of product market competition may be called a patchwork capitalism.
Keywords: E02; N14; P17; P51; 650; varieties of capitalism; institutions; CEE countries; post-communist capitalism